Dynamic Cycling State of Nonadiabatic Catalytic Combustion of Propylene - Suryo Purwono (ASEAN Journal of Chemical Engineering, 2006)
An experimental study of nonadiabatic fixed-bed reactor for controlling propylene gas was made under flow reversal operation. Temperature measurements were made within the catalyst and packing beds. The influence of the operating parameters on the shape of temperature profiles, conversion, and heat removal were studied. The experiments showed that the maximum measured reactor temperature and heat removal were rather insensitive to changes in cycle duration and sensitive to feed flow rate and reactant concentration. The simulation results for the variation of concentration, flow rate, and cycle time showed the experimentally observed behavior Further simulations showed that runaway can occur when concentration was high.